1988
DOI: 10.1042/bj2540835
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel thermostable β-amylase from Clostridium thermosulphurogenes

Abstract: An extracellular beta-amylase from Clostridium thermosulphurogenes was purified 811-fold to homogeneity, and its general molecular, physico-chemical and catalytic properties were determined. The native enzyme was a tetramer of 210 kDa composed of a single type subunit; its 20 amino acid N-terminus displayed 45% homology with Bacillus polymyxa beta-amylase. The beta-amylase was enriched in both acidic and hydrophobic amino acids. The pure enzyme displayed an isoelectric point of 5.1 and a pH activity optimum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…Advantages of using these thermostable and thermophilic enzymes in industrial processes were proposed (Zeikus, 1979;Ng & Kenealy, 1987). Our laboratory has reported on purification and biochemical characterization of thermostable fl-amylase and amylopullulanase from Clostridium thermosulfurogenes and C. thermohydrosulfuricum respectively Shen et al, 1988). In spite of the large number of studies on glucose isomerases from various enzyme sources, nothing is known about the detailed biochemical or molecular-genetic properties of glucose isomerases from thermoanaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of using these thermostable and thermophilic enzymes in industrial processes were proposed (Zeikus, 1979;Ng & Kenealy, 1987). Our laboratory has reported on purification and biochemical characterization of thermostable fl-amylase and amylopullulanase from Clostridium thermosulfurogenes and C. thermohydrosulfuricum respectively Shen et al, 1988). In spite of the large number of studies on glucose isomerases from various enzyme sources, nothing is known about the detailed biochemical or molecular-genetic properties of glucose isomerases from thermoanaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thermostable exo-acting β -amylases and glucoamylases are also available. β-amylases have for example been isolated from Thermotoga maritima [58] and Clostridium thermosulfurigenes [59,60]. The T. maritima enzyme has optimal activity at 95 °C and pH 5, while the C. thermosulfurigenes is optimally active at 75 °C, pH 5 although its stability is enhanced by Ca 2+ .…”
Section: Major Bottlenecksmentioning
confidence: 99%
“…The enzyme showed remarkable thermostability being fully active at 121°C for 15 min. Previously, a thermostable b amylase was isolated from Clostridium thermosulfurogenes by Shen et al (1988) that was stable at 80°C. Since thermostability is the crucial criteria for industrial application (Haki and Rakshit 2003), b amylase of this study has got a leading edge over all previously reported b amylase.…”
Section: Introductionmentioning
confidence: 99%